A REVIEW ON THE USE OF POLYETHYLENE TEREPHTHALATE (PET) AS AGGREGATES IN CONCRETE - Chowdhury, Tanvir Uddin; Mahi, Mahmud Amin; Azizul Haque, Kazi; Rahman, Md. Mostafizur (Malaysian Journal of Science, 2018)
ABSTRACT Massive amount of plastic and polymer products are being produced worldwide on a daily basis. Most of these are intended to be recycled, but the reality is quite different. Statistics show that the percentage of recyclable plastic and polymer products that are actually recycled is very insignificant. These plastic products are mostly non-biodegradable. As a result, they persist in the environment as potential pollutants. Hence there have been countless attempts to reuse these plastic products through versatile applications. This paper attempts to compile the studies which explored the reusability of plastic products in structural concrete. The principal focus will be on use of recycled Polyethylene Terephthalate (PET) in structural concrete in various forms. This study concludes that incorporating PET as a supplementary material in different forms has both beneficial and harmful impacts on various fresh and hardened properties of concretes and thus should be considered for comprehensive investigation. Keywords: PET; fresh concrete; concrete composites; supplementary materials; sustainable building material.